Case Study: Application of Seft Therapy (Spiritual Emotional Freedom Technique) on Sleep Pattern Disorders in Post-Op Laparotomy Patients (HEALTH CARE: JURNAL KESEHATAN, 2024)
Laparotomy is an operation performed to open the abdomen with an indication of a mass in the abdomen or bleeding. Post laparotomy surgery can cause complications such as infection and bleeding. The process of disease occurrence can affect sleep so that it prevents sleep and has an impact on sleep patterns. The purpose of this study was to determine the effect of SEFT (Spiritual Emotional Freedom Technique) therapy on disturbed sleep patterns in post-laparotomy clients. This research method uses a case study with a nursing care approach to Ny. M with sleep pattern disorders includes the provision of SEFT therapy interventions. Several studies related to SEFT therapy in sleep disorders have proven its effectiveness. The provision of nursing care is carried out on post-laparotomy clients with disturbed sleep patterns which is carried out for five days with a duration of 15-20 minutes of therapy, by measuring the results of sleep quality using the PSQI questionnaire before (the first day of therapy) and after (the next day after therapy). ). After the administration of SEFT therapy showed that the client's sleep quality improved. Based on the results of the application of nursing care, it is recommended that the next case study is expected to be used as a reference in similar case studies and be used as a reference for improvement in further research, as well as evaluations to focus more on clients when giving interventions so that therapy results are maximized.